In vitro assessment of the enzymatic degradation of several starch based biomaterials - Azevedo, Helena S. (2003)
The susceptibility of starch-based biomaterials to enzymatic degradation by amylolytic enzymes (glucoamylase and α-amylase) was investigated by means of incubating the materials with a buffer solution, containing enzymes at different concentrations and combinations, at 37 °C for 6 weeks. Two polymeric blends of corn starch with poly(ethylene-vinyl alcohol) copolymer and poly(Є-caprolactone), designated by SEVA-C and SPCL, respectively, were studied. The material degradation was characterized by gravimetry measurements, tensile mechanical testing, scanning electron microscopy (SEM), and Fourrier transform infrared-attenuated total reflectance (FTIR-ATR). The degradation liquors were analyzed for determination of reducing sugars, as a result of enzyme activity, and high performance anion exchange chromatography with pulsed amperometric detection (HPAEC-PAD) was used to identify the degradation products. All of the analysis performed showed that starch polymeric blends are susceptible to enzymatic degradation, as detected by increased weight loss and reducing sugars in solution. α-Amylase caused significant changes on the overall mechanical properties of the materials, with a decrease of about 65% and 58% being observed in the moduli for SEVA-C and SPCL, respectively, when compared with the control (samples incubated in buffer only). SEM analysis detected the presence of fractures and pores at the material’s surface as a result of starch degradation by amylolytic enzymes. FTIR spectra confirmed a decrease on the band corresponding to glycosidic linkage (-C-O-C-) of starch after incubation of the materials with α-amylase. In contrast, the incubation of the polymers in buffer only, did not cause significant changes on the material’s properties and morphology. Comparing the two materials, SEVA-C exhibited a higher degradability, which is related to the physicochemical structure of the materials and also to the fact that the starch concentration is higher in SEVA-C. The identification of the degradation products by HPAEC-PAD revealed that glucose was the major product of the enzymatic degradation of starch-based polymers. α-Amylase, as expected, is the key enzyme involved in the starch degradation, contributing to major changes on the physicochemical properties of the materials. Nevertheless, it was also found that starch-based polymers can also be degraded by other amylolytic enzymes but in a smaller extent.